2020
DOI: 10.3390/ijerph17062072
|View full text |Cite
|
Sign up to set email alerts
|

Gender-Related Differences in Flood Risk Perception and Behaviours among Private Groundwater Users in the Republic of Ireland

Abstract: Extreme weather events including flooding can have severe personal, infrastructural, and economic consequences, with recent evidence pointing to surface flooding as a pathway for the microbial contamination of private groundwater supplies. There is a pressing need for increasingly focused information and awareness campaigns to highlight the risks posed by extreme weather events and appropriate subsequent post-event actions. To date, little is known about the presence, directionality or magnitude of gender-rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 45 publications
(69 reference statements)
2
9
1
Order By: Relevance
“…These results appear to align with the available literature, that is dotted with reports on how gender actually influences the perception of risk and of personal risk [58,78,79], to the extent of altering the approach towards each phase of dealing with a disaster [80]. Nonetheless, such polarization of perception with gender is not always consistent [81] and it might also be affected by the conditions of the surrounding environment, especially in terms of exposure to recurring multiple hazards [82]. Finally, it has also been pointed out that gender might play a significant role in shaping risk perception and response due to the social construct related to it, in terms of norms, behaviors, attitudes and limitations [83].…”
Section: Perception Of Current and Future Impact Of Geohazardssupporting
confidence: 78%
“…These results appear to align with the available literature, that is dotted with reports on how gender actually influences the perception of risk and of personal risk [58,78,79], to the extent of altering the approach towards each phase of dealing with a disaster [80]. Nonetheless, such polarization of perception with gender is not always consistent [81] and it might also be affected by the conditions of the surrounding environment, especially in terms of exposure to recurring multiple hazards [82]. Finally, it has also been pointed out that gender might play a significant role in shaping risk perception and response due to the social construct related to it, in terms of norms, behaviors, attitudes and limitations [83].…”
Section: Perception Of Current and Future Impact Of Geohazardssupporting
confidence: 78%
“…This literature provided evidence that the level of perceived risk is not universally valid across individuals. In contrast, risk perception is influenced by a broad spectrum of variables including demographics (e.g., gender; Flynn et al., 1994; McDowell et al., 2020), ideologies (e.g., political orientation; Carlton & Jacobson, 2013; Peters & Slovic, 1996), and sociopsychological factors (e.g., environmental concerns; perceived controllability of the event; prior experience; Azadi et al., 2019; Kellstedt et al., 2008; Slimak & Dietz, 2006; Trumbo et al., 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Also, other recent studies addressing risk perceptions in regards to both traditional and emerging issues for public health such as COVID-19, chronic diseases and natural disasters (McDowell et al, 2020) have concluded that, beyond the average outcomes potentially observable between genders, the way that males and females develop risk-related appraisals of certain circumstances and individuals can largely vary in terms of nature, structure, and dynamics (Rhodes & Pivik, 2011;Useche et al, 2021). Indeed, various studies performed from the perspective of legal psychology in relation to other riskrelated issues, such as violence and aggression, do not only show how (from the earliest stages of development) gender may explain key behavioral differences, but how these discrepancies also apply to their attitudes and perceptions in regard to these risk-related behaviors (Del Hoyo-Bilbao et al, 2020;Loinaz & Sousa, 2019).…”
Section: Discussionmentioning
confidence: 99%